PERSEPSI KONSUMEN TERHADAP MAKANAN ORGANIK DI YOGYAKARTA - Waskito, Danang; Ananto, M; Reza, Andre (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Abstract The aim of this research is to reveal the perception of the consumers in Yogyakarta towards organic food. This research used a quantitative descriptive method with 118 respondents using a judgemental sampling technique. The consumers' perception toward organic food is referred to the perception toward health, quality, price, and food safety. The findings show that consumers in Yogyakarta have a high perception of organic food which is good for health as it has higher nutrition, can keep and increase the body imune.